2012
DOI: 10.4103/0974-8520.108854
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Tarakeshwara Rasa: An Ayurvedic herbomineral formulation

Abstract: Tarakeshwara Rasa (TR) is an Ayurvedic herbomineral compound formulation used in the intervention of Prameha vis-à-vis diabetes mellitus. The present study was executed to establish a fingerprint for this unique formulation, which can be adopted by the Ayurvedic pharmacies for drug standardization. TR is a formulation prepared by the trituration of four ingredients Abhraka Bhasma (AB), Loha Bhasma (LB), Vanga Bhasma (VB) and Rasa Sindhura (RS) in equal quantities with honey for one day. Each of the ingredients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The processing procedures for iron formulations (Lauha) are important for iron efficacy and safety [ 23 ]. The Ayurvedic medicine Tarakeswara Rasa is a metal mixture, and XRD analysis revealed that it contains Fe 2 O 3 (maghemite) in major phase, and SnO 2 (cassiterite), HgS, SiO 2 , and HgO in minor phases [ 24 ]. The preparation of Trivanga Bhasma (Sn, Zn and Pb), examined by XRD analysis, shows crystalline nature and nanosized particles by Scherrer's equation, and by SEM analysis, lead, zinc and tin oxides show well-defined plate-like structures [ 25 ].…”
Section: The Preparation Procedures Of Minerals In Ayurvedic and Tmentioning
confidence: 99%
“…The processing procedures for iron formulations (Lauha) are important for iron efficacy and safety [ 23 ]. The Ayurvedic medicine Tarakeswara Rasa is a metal mixture, and XRD analysis revealed that it contains Fe 2 O 3 (maghemite) in major phase, and SnO 2 (cassiterite), HgS, SiO 2 , and HgO in minor phases [ 24 ]. The preparation of Trivanga Bhasma (Sn, Zn and Pb), examined by XRD analysis, shows crystalline nature and nanosized particles by Scherrer's equation, and by SEM analysis, lead, zinc and tin oxides show well-defined plate-like structures [ 25 ].…”
Section: The Preparation Procedures Of Minerals In Ayurvedic and Tmentioning
confidence: 99%
“…Smaller particles may be because of presence of large quantity of Lauha bhasma and also due to presence of Swarna Makshika bhasma. The earlier SEM studies on Swarna Makshika bhasma reported that 1-2 μm and the particle size distribution of Lauha bhasma in a range of 2.5-40.9 μm 1 . Particle size depends on the nature of drug and calcination cycles.…”
Section: Discussionmentioning
confidence: 91%
“…Ancient scholars of Rasa Shastra have explained some tests (Bhasma parikshas) to identify the bhasmas. They may be classified into nondestructive (Nischandratvam, Rekhapurnata, Varitara, and Unama) and destructive (Apunarbhava and Niruttha) 1 . The prepared bhasma and purified Shilajit passed all the physio-chemical parameters of ancient classics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tarakeshwara Rasa contains calcined forms of tin, biotite and iron, as well as mercury in the form of mercuric sulfide or black sulfide of mercury along with other plant products. [ 6 ] Although scientists have expressed concerns on the use of heavy metals in the formulations and possible resultant toxicity, Ayurvedic practitioners insist that calcinations or use of metals such as mercury in particularly their sulfide form abolishes metal toxicity. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%